GAMBARAN BIAYA PERAWATAN STROKE DI RUANG PERAWATAN BAGIAN ILMU PENYAKIT SARAF RSUP CIPTO MANGUNKUSUMO - Ferdila Mariam*, Lyna Soertidewi*,Freddy Sitorus*, Joedo Prihartono** (NEURONA, 2010)
INTRODUCTION STROKE IS ONE OF THE MOST HEALTH PROBLEM THAT CAUSES ECONOMIC BURDEN HEALTHCARE SERVICES IS ESTABLISHING TO GET A BETTER STROKE MANAGEMENT AND EXPECTEDLY CAN REDUCE BURDEN OF DIRECT STROKE COSTS IN HOSPITAL